PENGARUH KOMPETENSI, KOMITMEN ORGANISASI, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI LAPAS NARKOTIKA KELAS IIA JAKARTA - Yosepha, Sri Yanthy; Erwanto, Yussiska Alex (Jurnal Ilmiah Manajemen SURYA PASCA SCIENTIA, 2024)
The study aims to prove the impact of competence, organization commitment, and work motivation on the performance of prison officials on 2a-class narcotics. The study employs a quantitative approach, survey methods, and path analysis. The population is 116 employees. With the simple sampling technique were acquired 88 respondents. The data was analyzed using excel and SPSS version 24.00. Studies show that: competence has a direct positive and significant impact on work motivation by 0,621; Organizational commitment affects immediate positive and significant motivation for work by 0,377; Competence affects immediate positive and significant performance by 0,195; Organizational commitment affects immediate positive and significant performance by 0,364; The motivation for work directly affected positive and significant the performance of the correctional officer in Jakarta at 0,452. Implications need to increase competence, organizational commitment, and work motivation.Keywords: competence, organizational commitment, work motivation, performance.